Principles of economics - Mankiw, N. Gregory (New Delhi, 2017)
Principles of Economics, sixth edition, became a best seller after its introduction and continues to be the most popular and widely used text in the economics classroom. Instructors found it the perfect complement to their teaching. A text by a superb writer and economist that stressed the most important concepts without overwhelming students with an excess of detail was a formula that was quickly imitated, but has yet to be matched. The sixth edition features a strong revision of content in all thirty-six chapters. Dozens of new applications emphasize the real-world relevance of economics for today$1 (Bs students through interesting news articles, realistic case studies and engaging problems. The premier ancillary package is the most extensive in the industry, using a team of instructors/preparers that have been with the project since the first edition.s
Keywords: Economics